A Rare Case of Perforated Descending Colon Cancer Complicated with a Fistula and Abscess of Left Iliopsoas and Ipsilateral Obturator Muscle - Alban Cacurri; Gaspare Cannata; Stefano Trastulli; Jacopo Desiderio; Antongiulio Mangia; Olga Adamenko; Eleonora Pressi; Giorgio Giovannelli; Giuseppe Noya; Amilcare Parisi (Case Reports in Surgery)
Perforation of descending colon cancer combined with iliopsoas abscess and fistula formation is a rare condition and has been reported few times. A 67-year-old man came to our first aid for an acute pain in the left iliac fossa, in the flank, and in the ipsilateral thigh. Ultrasonography and computed tomography revealed a left abdominal wall, retroperitoneal, and iliopsoas abscess that also involved the ipsilateral obturator muscle. It proceeded with an exploratory laparotomy that showed a tumor of the descending colon adhered and perforated in the retroperitoneum with abscess of the iliopsoas muscle on the left-hand side, with presence of a fistula and liver metastases. A left hemicolectomy with drainage of the broad abscess was performed. Pathologic report findings determined adenocarcinoma of the resected colon.